Diet pill and laxative use for weight control predicts first‐time receipt of an eating disorder diagnosis within the next 5 years among female adolescents and young adults. Issue 7 (5th May 2021) - Hazzard, Vivienne M.; Simone, Melissa; Austin, S. Bryn; Larson, Nicole; Neumark‐Sztainer, Dianne
Abstract: Objective: To replicate findings from a prior study which identified prospective associations between use of products for weight control and subsequent receipt of a first‐time eating disorder (ED) diagnosis among female adolescents and young adults. Method: Data from a prospective cohort study, Project EAT (Eating and Activity in Teens and Young Adults), were used to examine prospective associations between self‐reported past‐year diet pill and laxative use for weight control and self‐reported receipt of an ED diagnosis among females without prior receipt of an ED diagnosis ( N = 1, 015). Participants were followed from early/middle adolescence (EAT‐I; M age = 14.9 years) into late adolescence/emerging adulthood (EAT‐II; M age = 19.5 years) and young adulthood (EAT‐III; M age = 24.8 years). Results: First‐time receipt of an ED diagnosis was reported by 2.4% of participants at EAT‐II and 4.0% at EAT‐III. After adjusting for demographics and weight status, participants using diet pills (risk ratio [RR] = 3.58, 95% confidence interval [CI]: 1.96–6.54) and laxatives (RR = 2.77, 95% CI: 1.01–7.64) had greater risk of receiving a first‐time ED diagnosis within 5 years than those not using these products. Discussion: The present study replicated prior findings, providing further evidence for a prospective link between use of products for weight control and subsequent receipt of an ED diagnosis.